Law of the cloud: on the supremacy of the user interface over copyright law - Primavera De Filippi (Internet Policy Review)
Cloud computing technologies are commonly used for delivering content or information to users who no longer need to store this data onto their own devices. This is likely to have an important impact on the effectivity of copyright law in the context of online applications, insofar as the underlying infrastructure of the cloud is such that is allows cloud operators to control the manner in which and the extent to which users can exploit such content - regardless of whether it is protected by copyright law or it has already fallen in the public domain. This article analyses the extent to which the provisions of copyright law can potentially be bypassed by cloud computing applications whose interface is designed to regulate the access, use and reuse of online content, and how these online applications can be used to establish private regimes of regulation that often go beyond the scope of the traditional copyright regime.